2007
DOI: 10.1029/2007pa001422
|View full text |Cite
|
Sign up to set email alerts
|

A stratigraphically controlled multiproxy chronostratigraphy for the eastern Mediterranean

Abstract: [1] An Accelerator Mass Spectrometry (AMS) 14 C dated multiparameter event stratigraphy is developed for the Aegean Sea on the basis of highly resolved (centimeter to subcentimeter) multiproxy data collected from four late glacial to Holocene sediment cores. We quantify the degree of proportionality and synchroneity of sediment accumulation in these cores and use this framework to optimize the confidence levels in regional marine, radiocarbon-based chronostratigraphies. The applicability of the framework to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 47 publications
6
35
0
2
Order By: Relevance
“…The alignment resulted in age deviation outside the 2 σ range for two radiocarbon dates (deviation from the mean calibrated ages: 519 yrs in KL9 and 221 yrs in KL17 VL) (Table 1), whereas the remaining 13 AMS radiocarbon ages could be aligned within their 2 σ calibrated age range. This approach is similar to that of Casford et al [2007] in the eastern Mediterranean, where it has been shown that age uncertainties of individual AMS radiocarbon datings could amount to more than 1000 a, while the resulting mean offsets from a comprehensive age model were comparable to those found in our alignment. The resulting age model (Figure 4 and Table 1) spans 11.75 ka for KL17 VL (supported by the sapropel correlation with the well‐dated core GeoB 5844‐2 [ Arz et al , 2003a, 2003b]; Figure 3) and 10.6 ka for KL9 with the peak faunal transient around 2.4 ka BP, coinciding within age uncertainties to results of Edelman‐Furstenberg et al [2009].…”
Section: Resultssupporting
confidence: 84%
“…The alignment resulted in age deviation outside the 2 σ range for two radiocarbon dates (deviation from the mean calibrated ages: 519 yrs in KL9 and 221 yrs in KL17 VL) (Table 1), whereas the remaining 13 AMS radiocarbon ages could be aligned within their 2 σ calibrated age range. This approach is similar to that of Casford et al [2007] in the eastern Mediterranean, where it has been shown that age uncertainties of individual AMS radiocarbon datings could amount to more than 1000 a, while the resulting mean offsets from a comprehensive age model were comparable to those found in our alignment. The resulting age model (Figure 4 and Table 1) spans 11.75 ka for KL17 VL (supported by the sapropel correlation with the well‐dated core GeoB 5844‐2 [ Arz et al , 2003a, 2003b]; Figure 3) and 10.6 ka for KL9 with the peak faunal transient around 2.4 ka BP, coinciding within age uncertainties to results of Edelman‐Furstenberg et al [2009].…”
Section: Resultssupporting
confidence: 84%
“…2A). Detailed investigations of the S1 occurrence in these cores have been reported earlier (Casford et al, 2007;Kontakiotis et al, 2009Kontakiotis et al, , 2013Triantaphyllou et al, 2009a,b;Kontakiotis, 2012;Kouli et al, 2012). In NS-14, the most recent Z2 Santorini ash layer is positioned at 17 cm depth, and a sapropel-like, dark olive grey mud layer (Sapropel Mid Holocene e SMH) is deposited between 25 and 40 cm (Triantaphyllou et al, 2009a,b; (Fig.…”
Section: Study Sitesmentioning
confidence: 99%
“…For the age model of SK-1 core, bio-stratigraphic control also provides two well-dated correlation horizons, the biozone I/II and II/III boundaries of Jorissen et al (1993), which are useful chronologic standards for dating late Quaternary sequences in the central and eastern Mediterranean (including the Aegean Sea e Zachariasse et al, 1997;Casford et al, 2002;Geraga et al, 2010) due to their Mediterranean-wide applicability and synchroneity Hayes et al, 1999;Casford et al, 2001). Both age models previously published by Triantaphyllou et al (2009b) and Casford et al (2007) respectively have been tested against the multi-proxy chronological framework proposed by Casford et al (2007) for a generous number of sediment cores from the Aegean Sea. The ages in this study are given in calibrated ka BP.…”
Section: Time Stratigraphic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the first of these is well established at 5 to 6 centuries (Mercone et al 2000;Casford et al 2007), and it evidently forms part of a repeating RCC pattern during the Holocene. The GISP2 data ( Fig.…”
Section: The Aegean Recordmentioning
confidence: 95%